2022
DOI: 10.15282/ijhtc.v7i1.7498
|View full text |Cite
|
Sign up to set email alerts
|

Elemen-Elemen Keberkesanan Program Pengimarahan Masjid Era Kontemporari: Kajian Analisis Keperluan

Abstract: - In today's contemporary era, the function of the mosque should not be limited as a worship institution. In fact, the role of the mosque should be beyond the boundaries, which is the mosque should be an effective center for the development of muslim community. In this regard, a lot of efforts to strengthen the mosque programmes should be implemented consistently in order to meet the goals of the development for muslim community contemporary. In this aspect, this study seeks to identify the main elements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The function of the mosque as a place of worship is not limited to prayers, seclusion (iktikaf), study classes, and religious lectures alone. The mosque also plays a role in education, administration, community cohesion, politics, economic development, social affairs, and the spiritual and physical development of the Muslim community (Suhardi et al, 2022). The historical administration of Tanah Melayu has proven the significance of mosques as important institutions where mosques, suraus, or madrasahs serve as centers for education, the dissemination of Islam (Roslan & Tarmizi, 2011), and the development of the Muslim community and the splendor of Islamic civilization itself (Azlina et al, 2016).…”
Section: Advisor To the Mosques In The Mukimmentioning
confidence: 99%
“…The function of the mosque as a place of worship is not limited to prayers, seclusion (iktikaf), study classes, and religious lectures alone. The mosque also plays a role in education, administration, community cohesion, politics, economic development, social affairs, and the spiritual and physical development of the Muslim community (Suhardi et al, 2022). The historical administration of Tanah Melayu has proven the significance of mosques as important institutions where mosques, suraus, or madrasahs serve as centers for education, the dissemination of Islam (Roslan & Tarmizi, 2011), and the development of the Muslim community and the splendor of Islamic civilization itself (Azlina et al, 2016).…”
Section: Advisor To the Mosques In The Mukimmentioning
confidence: 99%
“…For instance, Rusli and Kadir [19] studied the reasons that caused new converts to return to their former religion due to lack of faith in Islam, insufficient knowledge of Islam, lack of religious commitment, marital issues, and conflict with their family. Additionally, Jusoh et al [20] identified seven main factors causing the low attendance of Muslims in the mosque, which are a limited function of the mosque, individual problems, inadequate basic facilities, non-strategic location, poor administrative and financial management as well as the personality of the mosque administrators. Suleiman and Farid [21] also investigated the factors contributing to the divorce rate among Muslim couples in Malaysia due to neglect of responsibility, infidelity, domestic violence, lack of understanding between spouses, financial problems, and third-party interventions.…”
Section: Introductionmentioning
confidence: 99%